FROM EDITOR - Surtiati, Rahayu (UI Scholars Hub, 2025)
Merry Christmas and a Happy New Year 2026. In this edition readers will find ten articles plus one book review proposing an idea of how culture survives modernization. The four articles (1, 2, 4, and 8 show how culture and ecology or culture and traditions can reshape collective memory and identity. Two articles: 6 and 7 discuss Japanese culture: first elderly people show learning a foreign language can keep their spirit of life; second Japanese urban culture in contemporary context. Last but not least three articles (3, 5, 9, and 10) describe three different situations: roads represent symbolic dimensions; priestly ministry and celibacy is more than just personal resilience; and regional culture learning in school is a way to understand the five principles of Pancasila.